Analisis Keuntungan Usaha Pengelolaan Cap Tikus Di Desa Raanan Baru Satu Kecamatan Motoling Barat Kabupaten Minahasa Selatan - Saroinsong, Loudewicjk Saul; Laoh, Olly Esry Harryani; Rori, Yolanda Pinky Ivanna (Sam Ratulangi University, 2023)
The purpose of this study is to analyze how much profit the Cap Tikus management business has in Raanan Baru Satu Village, West Motoling District, South Minahasa Regency. This research was carried out for 3 months from August to November 2022 at Raanan Baru Satu Village, West Motoling District, South Minahasa Regency. The data in this research was obtained from primary data and secondary data. Primary data is data obtained through direct interviews with 20 respondents, while secondary data is obtained from books, journals, village offices and agencies which can be used as data to support data collection in this research. This research was analyzed descriptively obtained from the data and presented in tabulation form with calculations of cost, revenue and income analysis. The results of this research are that the profits from the capticus management business in Raanan Baru Satu Village, West Motoling District, South Minahasa Regency can be said to be profitable with the average income for managing rat caps amounting to IDR 3,731,902.- per farmer and IDR 531,112.- per tree.